2010
DOI: 10.1038/nmeth.1500
|View full text |Cite
|
Sign up to set email alerts
|

Taming anxiety in laboratory mice

Abstract: Routine laboratory animal handling has profound effects on their anxiety and stress responses, but little is known about the impact of handling method. We found that picking up mice by the tail induced aversion and high anxiety, whereas use of tunnels or open hand led to voluntary approach, low anxiety and acceptance of physical restraint. Using the latter methods, one can minimize a widespread source of anxiety in laboratory mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
552
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 522 publications
(581 citation statements)
references
References 12 publications
24
552
1
4
Order By: Relevance
“…Our results show that restraint causes a maintained increase in both blood pressure and heart rate also following repeated exposures. It would be reasonable to conclude, based on these results, that restraint is particularly stressful to mice and may be an overriding factor in ameliorating any modifying effects of optimized handling and environmental conditions 13, 32. Moreover, it is standard to train mice so that they become accustomed to the investigator and total process; however, our results are similar to those obtained by others23, 24 in that no reduction in blood pressure or heart rate was seen as a result of repeated exposure to the technique.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Our results show that restraint causes a maintained increase in both blood pressure and heart rate also following repeated exposures. It would be reasonable to conclude, based on these results, that restraint is particularly stressful to mice and may be an overriding factor in ameliorating any modifying effects of optimized handling and environmental conditions 13, 32. Moreover, it is standard to train mice so that they become accustomed to the investigator and total process; however, our results are similar to those obtained by others23, 24 in that no reduction in blood pressure or heart rate was seen as a result of repeated exposure to the technique.…”
Section: Discussionmentioning
confidence: 96%
“…Hurst and West showed that when the mouse was picked up by the tail, greater anxiety is observed compared with when the mouse is lifted by a cupping technique or through use of a tube. In their study, anxiety was measured by a range of established anxiety assays 13. Here, we examined 3 handling techniques similar to those used by Hurst and West to determine whether any were preferable when using the tail‐cuff technique.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cold stress is controlled in maintaining the home cage or the experimental device on a heating plate [ 73 , 74 , 76 , 77 ] or under 60-W red bulbs suspended 20 cm above the device [ 78 , 79 ]. The handling method is essential to preserve mice from fear [ 80 ], and it is thus recommended to handle pups with extreme delicacy and consistency across experimenters to limit artifactual response variability. A protocol to familiarize pups with the experimental device can have positive effects on stress responses.…”
mentioning
confidence: 99%